2023
DOI: 10.1039/d2lc01033j
|View full text |Cite
|
Sign up to set email alerts
|

The 2D microfluidics cookbook – modeling convection and diffusion in plane flow devices

Abstract: A growing number of microfluidic systems operate not through networks of microchannels but instead using 2D flow fields. While the design rules for channel networks are already well-known and exposed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Evidently, the current model is still in a preliminary phase since numerous assumptions were made for closure, including the reduction of the 3‐D problem to 2‐D space, sharing of same viscosity between cell and cell‐encapsulating fluid, treatment of the cell as a homogeneous structure, and simplification of viscoelastic behavior of cell with linear elastic model. Additionally, the current 2‐D simulations show a good match to the experiment data as the experiment involved flow in a microfluidic chip, which is reasonably modelled by 2‐D profiles, 43 and the images were taken at the center plane. However, the agreement may deteriorate if the experiment data were examined in another focal plane, so a 3‐D representation of the flow is a necessary extension.…”
Section: Discussionmentioning
confidence: 59%
“…Evidently, the current model is still in a preliminary phase since numerous assumptions were made for closure, including the reduction of the 3‐D problem to 2‐D space, sharing of same viscosity between cell and cell‐encapsulating fluid, treatment of the cell as a homogeneous structure, and simplification of viscoelastic behavior of cell with linear elastic model. Additionally, the current 2‐D simulations show a good match to the experiment data as the experiment involved flow in a microfluidic chip, which is reasonably modelled by 2‐D profiles, 43 and the images were taken at the center plane. However, the agreement may deteriorate if the experiment data were examined in another focal plane, so a 3‐D representation of the flow is a necessary extension.…”
Section: Discussionmentioning
confidence: 59%
“…Gu Y et al have shown that for a microfluidic device with height <200 μm, there was minimum impact of convective flows in the channel . Boulais and Gervais have highlighted different devices and models and discussed the importance of chamber height and geometry . Koo and Kleinstreuer have described the impact of channel entrance and height, wall slip, and surface roughness factors on fluid flows in microchannels .…”
Section: Results and Discussionmentioning
confidence: 99%
“…31 Boulais and Gervais have highlighted different devices and models and discussed the importance of chamber height and geometry. 47 Koo and Kleinstreuer have described the impact of channel entrance and height, wall slip, and surface roughness factors on fluid flows in microchannels. 48 Beta et al have worked on understanding the impact of flow effects on cell/cell-like objects in microfluidic channels.…”
Section: Effect Of Presoaking and Spatiotemporal Dependencementioning
confidence: 99%
“…Diffusion‐limited regions are experimentally observed in multipolar devices (Goyette et al., 2019; Qasaimeh et al., 2011), and have been harnessed to generate tunable linear concentration gradients (Qasaimeh et al., 2011). In addition to improving our understanding of mass transfers between choriocapillaris and outer retina, the mathematical framework that we laid out in this study may therefore be used to inform the design of multipolar microfluidic systems, with applications ranging from the study of cell chemotaxis, single‐cell analyses (Boulais & Gervais, 2023), and groundwater, hydrocarbon and geothermal heat recovery (Koplik et al., 1994; Kurowski et al., 1994; Zhang & Koplik, 1997).…”
Section: Discussionmentioning
confidence: 99%